Coexistent anemia modulates systemic inflammation and exacerbates disease severity and adverse treatment outcomes in tuberculosis - Dasan, Bindu; Munisankar, Saravanan; Pavan Kumar, Nathella; Moideen, Kadar; Pandiarajan, Arul Nancy; Nott, Sujatha; Viswanathan, Vijay; Shanmugam, Sivakumar; Hissar, Syed; Thiruvengadam, Kannan; Kornfeld, Hardy; Babu, Subash (Frontiers in Tuberculosis, 2025)
IntroductionAnemia has been shown to be an independent predictor of disease progression and death in tuberculosis (TB) patients, significantly impacting TB in several ways. This dual burden poses significant challenges for TB control efforts. However, the mechanism by which anemia influences disease severity, bacterial burden, and TB treatment outcomes remains poorly understood.MethodsIn this study, we aimed to compare bacterial burdens, disease severity, and TB treatment outcomes in TB patients with or without anemia. Participants were recruited from Chennai, South India, as part of the prospective Effect of Diabetes on Tuberculosis Severity (EDOTS) study conducted from February 2014 to August 2018. Anemia was defined as hemoglobin (Hb) levels <13 g/dL and <12 g/dL for males and females, respectively. We employed chest X-rays to assess bilateral lung and cavitary diseases and sputum smear grades to measure bacterial loads in TB subjects. Treatment outcomes were defined as favorable or unfavorable. Cytokine profile was measured using multiplex ELISA.ResultsThe study comprised of 483 culture-confirmed TB individuals, with 288 positives for anemia {Median Hb was 11.0 [interquartile range (IQR)], 10.3–12.3} and 195 negatives [Median Hb was 14.3 (IQR), 13.5–15.2]. The study revealed that TB patients with anemia had significantly higher bacterial loads [adjusted prevalence ratio (aPR), 4.01; 95% CI, 2.22–6.63; p < 0.001], cavitary lung lesions [aPR, 3.36; 95% CI, 1.95–5.68; p < 0.001] and unfavorable treatment outcomes [aPR, 1.61; 95% CI, 1.31–2.19; p = 0.046] compared to those without anemia. Our data also show that TB is associated with significantly lower levels of type-1 cytokines (IFNγ and IL-2) but significantly higher levels of pro-inflammatory cytokines (IL-6, IFNα, and IFNβ) and pro-fibrotic factors (VEGF, EGF, FGF-2, and PDGF-AB/BB) in anemic individuals compared to those without anemia.ConclusionsThese findings highlight a clear association between anemia and increased TB severity, elevated bacterial loads, and poor treatment outcomes. Our data also suggest that anemia might be associated with the modulation of cytokine responses, which could impart a detrimental effect on TB pathogenesis.